The use of simulation technique among undergraduate nursing student - Nurumal, Mohd. Said; Mohamad Azizi, Mohammad Syafiq; Che Hasan, Muhammad Kamil (2020)
Introduction. Simulation is widely practised as learning strategies in many disciplines including nursing. It is considered an updated technological approach towards providing safe and sound patients care. Thus, this study was conducted to assess the level of knowledge among nursing students using a simulated mannequin for cardiovascular assessment. Methods. This is a cross-sectional study design focusing Year 4 nursing students at Kulliyyah of Nursing, International Islamic University Malaysia (IIUM). A simulation mannequin was used for students performing a cardiovascular assessment. Level of knowledge was tested using an adapted questionnaire. The study was approved by the Kulliyyah of Nursing Postgraduate Research Committee (Ref: IIUM/313/DDAA/20/4/10) and IIUM Research Ethics Committee (Ref: IREC 2018-024). Results. A total of 57 nursing students involved in this study revealing 100% good level of knowledge for cardiovascular assessment. Fifty-two of them reported that simulation exercise is one of the good learning strategies to enhance their capabilities and increase their confidence level. Conclusions. The results from this study could indicate that using technological simulation approach could provide a similar effect in performing cardiovascular assessment among nursing student IIUM. Future larger scale is needed including any other sub-disciplines in nursing to facilitate students' preparation towards the real clinical setting.